(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
In preschool educational organizations, educators are provided with information about a deep knowledge of the content and essence of Uzbek national musical works, along with musical works of other peoples, as well as their role in their creations, as well as their practical application.